IMPLEMENTASI MODEL BELAJAR CTL DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MAPEL AQIDAH AKHLAK DI MAN 3 JOMBANG - Fadilah Muiz Firdausi; Burhanuddin Ridlwan; Laily Masruroh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Contextual Teaching and Learning learning model is learning about the connection between the material being studied by students and the students' living environment. Student learning outcomes are a manifestation of learning behavior which is usually manifested in the form of student changes. And student success can be seen in monitoring the learning process. This thesis research uses a case study type of research and the research approach is a qualitative descriptive approach. The data collection techniques used are observation, interviews and documentation. The results of the research show that the implementation of the contextual teaching and learning model in improving student learning outcomes in the moral aqidah subject at MAN 3 Jombang is: 1). The implementation of the CTL learning model at MAN 3 Jombang, namely that learning must be contextualized with everyday life, 2). The implementation of the CTL learning model in improving student learning outcomes in the moral aqidah subject at MAN 3 Jombang is that basically in a lesson it must be practiced, and practiced is what is called contextual. In delivering lesson material, examples are also given from real stories from the teacher's daily life or phenomena that are currently hotly discussed on social media, 3). Supporting factors and inhibiting factors for the implementation of the CTL learning model in improving student learning outcomes in the moral aqidah subject at MAN 3 Jombang, namely the supporting factors are adequate infrastructure and increasing teacher competency. Meanwhile, the inhibiting factor is stimulating students' interest in learning.